2009
DOI: 10.1289/ehp.0800058
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to a Brominated Flame Retardant and Genitourinary Conditions in Male Offspring

Abstract: BackgroundThe upward trend in industrial nations in the incidence of male genitourinary (GU) conditions may be attributed to increased exposure to endocrine disruptors. Polybrominated biphenyl (PBB), a brominated flame retardant, is one such suspected endocrine disruptor.ObjectiveWe investigated the relationship between maternal serum levels of PBBs and GU conditions among male offspring exposed in utero.MethodsIn this cohort study of sons born to women accidentally exposed to PBBs during 1973–1974, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…(2012)USA (12 centers)Collaborative Perinatal Project197/557Third trimester serumHighest quartile versus lowest trans -nonachlor1.080.62–1.89Yes90Oxychlordane1.240.69–2.22Yes9Bhatia et al . (2005)USA, San FranciscoChild Health and Development Study66/283Maternal serumHighest versus lowest quartilep,p′-DDT0.790.33–1.89Yes90p,p′-DDE1.180.46–3.02Yes90Small et al . (2009)USA, MichiganMichigan Long-term PBB Study14/431Maternal serumHighest versus lowest (<LOD).…”
Section: Methodsmentioning
confidence: 99%
“…(2012)USA (12 centers)Collaborative Perinatal Project197/557Third trimester serumHighest quartile versus lowest trans -nonachlor1.080.62–1.89Yes90Oxychlordane1.240.69–2.22Yes9Bhatia et al . (2005)USA, San FranciscoChild Health and Development Study66/283Maternal serumHighest versus lowest quartilep,p′-DDT0.790.33–1.89Yes90p,p′-DDE1.180.46–3.02Yes90Small et al . (2009)USA, MichiganMichigan Long-term PBB Study14/431Maternal serumHighest versus lowest (<LOD).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the critical level of exposure to EDCs was not assessed in any of the epidemiological studies implicating the environment [67] [125]. No relationship was identified between polybrominated biphenyl (PBB) [127] or polychlorinated biphenyl (PCB) exposure [128] and hypospadias. A recent meta-analysis indicated only a modestly increased risk of hypospadias associated with pesticide exposure [129].…”
Section: Limitations and Questionsmentioning
confidence: 99%
“…Not only were a large proportion of the reported data below the LOD but this also precluded evaluation of individual congener associations, which may contribute differently to toxicity and to related health outcomes. Even with such limited exposure characterization, research with this population has demonstrated intergenerational transfer of PBBs (12) and exposure-related health effects including poorer neonatal health (13), adverse reproductive outcomes (14), menstrual irregularities (15), accelerated pubertal development among females (16), increased incidence of urogenital problems (17), slower growth among males (18) and risk of digestive cancer and lymphoma (19) as well as a non-statistically significant increased incidence of breast cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%